1976
DOI: 10.1007/bf00917765
|View full text |Cite
|
Sign up to set email alerts
|

Overselectivity, developmental level, and overtraining in autistic and normal children

Abstract: Thirteen autistic children were compared to 13 normal children matched to them in mental age, on performance of a visual discrimination task. Form, color, and size were relevant and redundant cues. The groups did not differ significantly in mean trials to reach criterion or in breadth of learning, and both groups increased their breadth of learning after 50 trials of overtraining. Form was preferred to color and size by both autistic and normal children. Within each group, rank on mental age was highly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 13 publications
4
45
0
Order By: Relevance
“…Once the criterion was met, subjects proceeded immediately to the next phase of training or to testing. This may have precluded overtraining, which can alter the performance of severely handicapped individuals (Shover & Newsom, 1976). Had the training been greatly extended, the language-disabled children might have shown the development of equivalence classes.…”
Section: Discussionmentioning
confidence: 99%
“…Once the criterion was met, subjects proceeded immediately to the next phase of training or to testing. This may have precluded overtraining, which can alter the performance of severely handicapped individuals (Shover & Newsom, 1976). Had the training been greatly extended, the language-disabled children might have shown the development of equivalence classes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a product of the sample in the second experiment simultaneously having a higher chronological age, and a lower mental age, than those in Experiment 1, which would produce a lower IQ score. Over-selectivity has been noted previously to be correlated with both lower mental ages and lower IQ scores (see Schover & Newsom, 1976;Wilhelm & Lovaas, 1976).…”
Section: Leader Et Al -14 ----------------------------Figure 2 Aboutmentioning
confidence: 99%
“…In this experiment, an older sample was employed to establish the generality of the effect for people with ASD, as age has previously been linked to the emergence of over-selectivity (Schover & Newsom, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…These criteria were chosen for two major reasons. The 125 correct responses were chosen as a criterion in order to overtrain the discriminations used in this investigation, because previous research has demonstrated that overtraining is an important variable in reducing stimulus overselectivity in autistic children (e.g., Koegel, Schreibman, Britten, & Laitinen, 1979;Schover & Newsom, 1976). The other criterion, failure to respond for three consecutive trials, was used to indicate the occurrence of satiation, because previous work with these children on other tasks indicated that initial failures to respond preceded cessation of responding.…”
Section: Constant Reinforcer Conditionmentioning
confidence: 99%